2016
DOI: 10.18632/oncotarget.12434
|View full text |Cite
|
Sign up to set email alerts
|

CCND1 mutations increase protein stability and promote ibrutinib resistance in mantle cell lymphoma

Abstract: Mantle cell lymphoma (MCL) is characterized by the t(11;14) translocation, which leads to deregulated expression of the cell cycle regulatory protein cyclin D1 (CCND1). Genomic studies of MCL have also identified recurrent mutations in the coding region of CCND1. However, the functional consequence of these mutations is not known. Here, we showed that, compared to wild type (WT), single E36K, Y44D or C47S CCND1 mutations increased CCND1 protein levels in MCL cell lines. Mechanistically, these mutations stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 42 publications
1
39
0
Order By: Relevance
“…Recently, WES and RNA‐sequencing analysis revealed exon 1 CCND1 mutations in 14–34% of cases . These mutations lead to stabilized nuclear cyclin D1 protein , and have also been detected in 18% of the nnMCL subtype . Of interest, a small subset of SOX11‐positive MCL without the t(11;14) has been recognized (~5% of MCL), and more than half carry CCND2 gene rearrangements as alternative mechanism to CCND1 translocation .…”
Section: Mantle Cell Lymphomasmentioning
confidence: 99%
“…Recently, WES and RNA‐sequencing analysis revealed exon 1 CCND1 mutations in 14–34% of cases . These mutations lead to stabilized nuclear cyclin D1 protein , and have also been detected in 18% of the nnMCL subtype . Of interest, a small subset of SOX11‐positive MCL without the t(11;14) has been recognized (~5% of MCL), and more than half carry CCND2 gene rearrangements as alternative mechanism to CCND1 translocation .…”
Section: Mantle Cell Lymphomasmentioning
confidence: 99%
“…A novel mechanism of ibrutinib resistance in MCL may be through mutations of CCND1 . In vitro studies in cell lines and primary MCL cells have shown that CCND1 mutations increase the stability of CCND1 protein and cause ibrutinib resistance . More data on the mechanisms of resistance are expected to be gained from patients who are progressing on ibrutinib in the ongoing RAY trial.…”
Section: Mantle Cell Lymphomamentioning
confidence: 99%
“…Primary resistance to ibrutinib might be caused by diverse pathogenic mechanisms such as PIK3‐AKT pathway activation and activation of the NFkB pathways . Moreover, increased expression of cyclin D1 (CCND1) gene due to mutations or forced expression of the wild‐type gene could lead to increased resistance of MCL cell . In our patient, the immunohistochemistry showed that the expression of CCND1 was strongly positive at the start of the treatment with obinutuzumab and venetoclax.…”
Section: Resultsmentioning
confidence: 99%